In vitro multiplication and rooting of Fragaria x ananassa Duch. Var. ‘Aromas’ - Romero Rivas, Ladislao Cesar (2023)
Strawberry (Fragaria x ananassa Duch.) is an important fruit for human consumption. It is  species are vegetatively propagated by runners. At present, micropropagation is the most suitable way of commercial strawberry propagation. It is possible to produce disease-free plants through micropropagation. Plant growth regulators play an essential role in micropropagation of plants with traits of agronomic interest. The objective of this study was to develop a protocol for shoot multiplication and in vitro rooting of strawberry var. ‘Aromas’, using shoot buds as explants, cultivated in MS medium supplemented with different concentrations of plant growth regulators. For shoot multiplication, in vitro shoot clusters were used and cultivated in MS medium supplemented with different auxin and cytokinin concentrations. Shoots obtained in the best multiplication treatment after two months of cultivation, were used as a source of explants for in vitro rooting. The experiment was set up in a randomized complete block design. In multiplication phase number and length of shoots, and leaves per explant were measured. In rooting phase, root number per shoot and root length were recorded. MS medium supplemented with different concentration of BAP in combination with KIN and IAA showed no significant difference in terms of shoot number and shoot quality. In vitro rooting in MS medium with no growth regulators added, reached the best rooting formation, compared with the treatments with IBA and NAA. This demonstrate that explants used for in vitro rooting had enough endogenous plant growth regulators for rooting formation.